Transcriptional analysis of the cell division-related ssg genes in Streptomyces coelicolor reveals direct control of ssgR by AtrA - Kim, Songhee H. (Antonie Van Leeuwenhoek, 2015)
SsgA-like proteins are a family of actinomycete-specific regulatory proteins that control cell division and spore maturation in streptomycetes. SsgA and SsgB together activate sporulation-specific cell division by controlling the localization of FtsZ. Here we report the identification of novel regulators that control the transcription of the ssgA-like genes. Transcriptional regulators controlling ssg gene expression were identified using a DNA-affinity capture assay. Supporting transcriptional and DNA binding studies showed that the ssgA activator gene ssgR is controlled by the TetR-family regulator AtrA, while the γ-butyrolactone-responsive AdpA (SCO2792) and SlbR (SCO0608) and the metabolic regulator Rok7B7 (SCO6008) were identified as candidate regulators for the cell division genes ssgA, ssgB and ssgG. Transcription of the cell division gene ssgB depended on the sporulation genes whiA and whiH, while ssgR, ssgA and ssgD were transcribed independently of the whi genes. Our work sheds new light on the mechanisms by which sporulation-specific cell division is controlled in Streptomyces. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s10482-015-0479-2) contains supplementary material, which is available to authorized users.